2006
DOI: 10.1017/s1138741600006041
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Content and Physical Properties of Affective Pictures on Emotional Responses

Abstract: The aim of this research was to study the influence of both the emotional content and the physical characteristics of affective stimuli on the psychophysiological, behavioral and cognitive indexes of the emotional response. We selected 54 pictures from the IAPS, depicting unpleasant, neutral, and pleasant contents, and used two picture sizes as experimental conditions (120 × 90 cm and 52 × 42 cm). Sixty-one subjects were randomly assigned to each experimental condition. We recorded the startle blink reflex, sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 35 publications
3
8
2
3
Order By: Relevance
“…Previous picture studies (Bradley et al, 2001b) found similar results in subjective ratings, in which women judged unpleasant pictures as more unpleasant and arousing compared to men who rated erotic material as more arousing and pleasant than women did. In spite of gender differences in subjective reports, men and women are quite similar in their affective physiological reactions to pleasant and unpleasant stimuli (Bradley et al, 2001b;Caseras et al, 2007;Frazier et al, 2004;Kreibig et al, 2007;Sanchez-Navarro and Martinez-Selva, 2006;Wrase et al, 2003). Moreover, although recent functional imaging studies found gender differences in amygdala and extrastriate visual cortex activation in reaction to emotional stimuli (pictures or films), these gender differences were not observed in terms of autonomic changes (Caseras et al, 2007;Hamann et al, 2004;Sabatinelli et al, 2004;Wrase et al, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…Previous picture studies (Bradley et al, 2001b) found similar results in subjective ratings, in which women judged unpleasant pictures as more unpleasant and arousing compared to men who rated erotic material as more arousing and pleasant than women did. In spite of gender differences in subjective reports, men and women are quite similar in their affective physiological reactions to pleasant and unpleasant stimuli (Bradley et al, 2001b;Caseras et al, 2007;Frazier et al, 2004;Kreibig et al, 2007;Sanchez-Navarro and Martinez-Selva, 2006;Wrase et al, 2003). Moreover, although recent functional imaging studies found gender differences in amygdala and extrastriate visual cortex activation in reaction to emotional stimuli (pictures or films), these gender differences were not observed in terms of autonomic changes (Caseras et al, 2007;Hamann et al, 2004;Sabatinelli et al, 2004;Wrase et al, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…Delplanque et al (2007) showed that some of the negative stimuli contained in the international affective picture system (IAPS) have a higher fraction of lower spatial frequency as compared to neutral ones. Meanwhile, however, it has been shown that the emotional effect is not solely explained by physical properties De Cesarei and Codispoti, 2006;Sánchez-Navarro et al, 2006) and studies which carefully controlled their visual stimulus material for physical characteristics still report strong emotional effects (Junghofer et al, 2001(Junghofer et al, , 2006Keil et al, 2003;Sabatinelli et al, 2007).…”
Section: Emotional Stimuli: Inherent Physical Properties or Not?mentioning
confidence: 99%
“…In turn, heart-rate change has shown a significant positive relation to affective valence, with unpleasant pictures prompting slower heart rates than pleasant ones (Greenwald et al, 1989;Lang et al, 1993). However, several studies (e.g., Bradley, Lang, & Cuthbert, 1993;Cuthbert, Bradley, & Lang, 1996;Lang et al, 1993;Sánchez-Navarro, Martínez-Selva, Román, & Torrente, 2006) have also found a relationship between heart rate and arousal, with the most arousing pictures (pleasant and unpleasant) prompting the highest heart-rate deceleration.…”
mentioning
confidence: 99%